2015
DOI: 10.1007/s12519-015-0073-8
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive uropathy and severe acute kidney injury from renal calculi due to adenine phosphoribosyltransferase deficiency

Abstract: APRT deficiency should be considered in patients with multiple radiolucent renal calculi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…He first presented acutely when he was 17 months' old with obstructive uropathy requiring continuous kidney replacement therapy (CKRT) and surgical removal of kidney calculi. 9 He was diagnosed with APRT deficiency when stone analysis performed via infrared spectrometry demonstrated that the presence of (p.Leu162del) is not present in population databases (gnomAD) 10 and has not been reported before in patients with APRT deficiency. In addition, there is lack of computational and functional evidence to support the pathogenicity of the variant, this variant was classified as variant of uncertain significance at the time of testing.…”
Section: Clinical Descriptionmentioning
confidence: 97%
See 1 more Smart Citation
“…He first presented acutely when he was 17 months' old with obstructive uropathy requiring continuous kidney replacement therapy (CKRT) and surgical removal of kidney calculi. 9 He was diagnosed with APRT deficiency when stone analysis performed via infrared spectrometry demonstrated that the presence of (p.Leu162del) is not present in population databases (gnomAD) 10 and has not been reported before in patients with APRT deficiency. In addition, there is lack of computational and functional evidence to support the pathogenicity of the variant, this variant was classified as variant of uncertain significance at the time of testing.…”
Section: Clinical Descriptionmentioning
confidence: 97%
“…Patient 1 was previously well with no medical issues and was thriving. He first presented acutely when he was 17 months' old with obstructive uropathy requiring continuous kidney replacement therapy (CKRT) and surgical removal of kidney calculi 9 . He was diagnosed with APRT deficiency when stone analysis performed via infrared spectrometry demonstrated that the presence of DHA and red blood cell enzyme assay showed very low APRT activity (0.03 nmol/min/mg haemoglobin, normal 0.15–2.0 nmol/min/mg haemoglobin, residual enzyme activity: 3%).…”
Section: Clinical Descriptionmentioning
confidence: 99%
“…There was a previous case report of APRT deficiency in a 17-month-old Chinese boy presenting with severe acute kidney injury secondary to obstructive uropathy from multiple renal calculi. 11 However, no genetic study was reported as the diagnosis was only made by infrared spectrometric stone analysis and red blood cell enzyme assay. Genetic characterisation would be helpful for better understanding of the genetic basis of APRT deficiency in the Chinese population and molecular testing strategy.…”
Section: Laboratory Diagnosis Of Aprt Deficiency Requiresmentioning
confidence: 99%
“…Adenine crystals are directly toxic to renal tubules during their accumulation and excretion into urine, which can cause obstruction of renal tubules and lead to AKI. 22 Therefore, in this study, an adenine-induced AKI mouse model was used to evaluate the therapeutic effects of B. bifidum FL228.1, FL276.1 and ZL.1 from different sources on the kidneys and intestines of AKI mice. By detecting the serum inflammation level, the intestinal barrier function and the gut microbiota composition, we explored the potential mechanism of action of Bifidobacterium in improving AKI mice.…”
Section: Introductionmentioning
confidence: 99%